PENGEMBANGAN MODEL PEMBELAJARAN IPS PADA KURIKULUM 2013 DI JENJANG PENDIDIKAN SEKOLAH DASAR - Safrudin Safrudin (JURNAL PENDIDIKAN ROKANIA, 2016)
Implementation of curriculum 2013 that applied to school and madrassa has its own characteristics. Likewise the learning model is applied to the new curriculum. Learning model as a conceptual framework that describes a systematic procedure in organizing learning experiences to achieve specific learning objectives, and serves as a guideline for the designers of learning and teachers in planning and implementing learning activities. The learning model is a very important thing to be noticed by implementing learning. Teachersare the spearhead ofimplementinglearning in the classroom. Learning success or failure is entirely in the hands of teachers, especially in social science learning. On the Elementry / Islamic Elementary social studies contain material geography, history, sociology, and economics. Social science subjects are arranged in a systematic, comprehensive, and integrated in the learning process towards maturity and success in life in society. By studying the social science is expected to learners will gain a wider understanding and depth in science-related fields.